História e vida: o encontro epistemológico entre Didática da História e Educação Histórica - Alves, Ronaldo Cardoso [UNESP] (Universidade Estadual de Londrina, 2013)
The article gives a brief history about the formation of the scientific field of Didactic of History in Germany, as well as History Education in England and his epistemological meeting, occurred early in this century. Secondly, part of epistemology to relate historical knowledge, scientifically designed, the guidance needs of humans in quotidian Contemporary Historical Culture. Finally, it presents such a meeting as a supplier of a theoretical-methodological repertoire that enables the qualification of research Teaching of History in Brazil, aiming to research about the school as a place of development of historical consciousness of students and teachers.

O artigo faz um breve histórico acerca da formação do campo científico da Didática da História na Alemanha, bem como da History Education na Inglaterra e o encontro epistemológico dessas vertentes, ocorrido no início do século XXI. Num segundo momento, parte desta epistemologia para relacionar o conhecimento histórico, cientificamente concebido, às necessidades de orientação dos seres humanos no cotidiano da Cultura Histórica contemporânea. Finalmente, apresenta tal encontro como fornecedor de um repertório teórico-metodológico que possibilita a qualificação das pesquisas de Ensino de História no Brasil, com vistas à investigação a respeito da escola como lugar de desenvolvimento da consciência histórica de estudantes e professores.
Keywords: Historical consciousness; Didactic of history; Philosophy of history; History education; History culture; Consciência histórica; Didática da História; Filosofia da História; Educação histórica; Cultura histórica